HIV/AIDS in Migrant People of Dang District of Nepal - Oli, Karna Bahadur; Maharjan, Mahendra (Journal of Institute of Science and Technology, 2015)
Present status of HIV/AIDS among the migrant people of Dang district along with Knowledge, Attitude and Practices (KAP) was assessed by blood testing and questionnaire survey. A total of 1102 blood samples from migrants as well as spouse of migrants were tested for HIV using Rapid Diagnostic Test (RDT) kits as recommended by national HIV testing protocol. The overall HIV prevalence was found to be 0.6% in Dang district during the year 2012 – 2013. Migrants and spouse of migrants were infected in the equal ratio (0.3%). Maximum of the participants were among the age group 18-34 years and most of them had attained lower secondary level education. Maximum (97.3%) respondents had knowledge about the family planning methods and practice of condom use among the married population was also satisfactory. About 16% of the participants had expressed their practice of sexual relationship outside more than once, which signifies vulnerability to HIV infection. Maximum married females were suffered from Sexually Transmitted Infections (STI) which may lead to infection such as Syphilis and HIV/AIDS. Journal of Institute of Science and Technology, 2014, 19(2): 71-75